The successful novelist ebook A lifetime of lessons about writing and publishing. - Morrell, David (2008)
Learn how to write a novel from a New York Times bestselling and award-winning author with more than fifty years of writing and publishing experience. The Successful Novelist is one of the best books on writing fiction for aspiring and experienced writers alike. David Morrell, bestselling author of First Blood, The Brotherhood of the Rose, and The Fifth Profession, tackles everything from the craft of writing and dealing with writer's block to the psychology of being a fiction writer and how to market a book. By reading this book, you'll learn how to overcome common obstacles standing in your way of becoming a successful novelist and creating better fiction in the process. Plus, it's great reference guide if you're participating in NaNoWriMo! Topics covered include: Novel plotting Story structure Character development How to write dialogue Book research Viewpoint/POV Writing descriptions Succeeding in publishing And more! Praise for The Successful Novelist: "Like listening to a beloved brother. I found the acute observations and his narrative philosophy more valuable for the new writer than the contents of any 100 other texts."—Dean Koontz, international bestselling author whose books have sold over 500 million copies "This is the best guidebook to both writing and the business of writing that I've ever read."—Peter Straub, award-winning novelist and poet "The Successful Novelist is the vehicle you want if you plan to drive your way to successful fiction."—Joe R. Lansdale, award-winning author of 45 novels